Quality of life among caregivers of patients with end-stage renal disease in Hospital Universiti Sains Malaysia - Zul, Nurul Fatihah (2020)
QOL is defined as an individual’s perception of their position in life in the context of culture and value system where they live, and in relation to their goals, expectations, standards, and concerns. Caregivers play an important role in providing care to patients with ESRD and help them to adapt and manage their chronic illnesses. This study aimed to determine the level of QOL among caregivers and the association between selected sociodemographic data and the level of QOL among caregivers in HUSM. A cross-sectional study was conducted among caregivers of patients with ESRD using self-administered questionnaire. One-way ANOVA was used to find the association between selected demographic data and the level of QOL among caregivers in HUSM with significance at p < 0.05. There were 40 respondents who was involved. The finding shows 23 (57.5%) of caregivers has rate their level QOL as good and 27 (67.5%) were satisfied in their health. The highest mean score of QOL were in the domain social (mean 3.93, SD = 0.50). There was a significant mean difference between education level and the level of QOL in domains physical (p = 0.019) and environment (p = 0.006). Next, there was a significant mean difference between the age of the patient and the level of QOL in physical domain (p = 0.024). Lastly, there was a significant mean difference between the length of the patient with ESRD receiving HD and the level of QOL in environment domain (p = 0.043). In conclusion, physiological domain was significantly the most affected domain in the level of QOL among caregivers. The physical and environment domain were most affected domains as associated with sociodemographic variable. Nurses have a big responsibility to improve the life of caregivers to have a better QOL.